Fuzzy-pid control of transverse vibrating pipe due to vortex induced vibration - Shaharuddin, N. M. R. (2013)
This paper presents the fuzzy-PID control of flexibly mounted rigid pipe which undergoes vortex induced vibration phenomena. The cylinder is allowed to move in one direction which is perpendicular to the flow direction. The input and output data are obtained from experimental works where the input is the current flow speed and the output is the acceleration of the pipe. Auto-Regressive External Input (ARX) model is used as the transfer function structure whereas Recursive Least Square (RLS) technique is adopted in order to determine the parameter of the ARX model. Fuzzy-PID controller are developed and applied to the vibrating system that represented by the ARX model. Two types of external disturbances are applied in order to determine the robustness of the controller. It was shown that the developed controller successfully attenuate the vibration of the system, regardless the type of external disturbance exerted to the system.